Percutaneous mechanical thrombectomy versus catheter-directed thrombolysis for the treatment of arterial acute mesenteric ischemia and risk factors for 30-day mortality - Shi, Yadong; Zhou, Yangyi; Huang, Hao; Chen, Liang; Su, Haobo; Gu, Jianping (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveTo compare the efficacy and safety outcomes between percutaneous mechanical thrombectomy (PMT) and catheter-directed thrombolysis (CDT) as the first endovascular revascularization (EVR) strategy for arterial acute mesenteric ischemia (AMI) and identify risk factors for 30-day mortality.MethodsThis was a single-center retrospective study. Between May 2014 and March 2024, consecutive patients with arterial AMI who received EVR using PMT or CDT as the first strategy were included. The baseline characteristics, imaging information, procedure-related information, complications, and clinical outcomes of patients were analyzed and compared. Binary logistic regression analysis was used to identify potential risk factors for 30-day mortality with an odds ratio (OR) and 95% confidence interval (CI).ResultsForty-seven patients (PMT, n = 29; CDT, n = 18) were included. The mean age was 74.3 ± 7.6 years, and 66.0% were female. Successful revascularization was achieved in 89.4% of patients, and the 30-day mortality rate was 31.9%. There was no significant difference in successful revascularization, complications, and clinical outcomes between PMT and CDT as the first strategy. High plasma lactate (adjusted OR 1.73 per 1.0 mmol/L increase, 95% CI: 1.13–2.66; p = 0.012) and D-dimer (adjusted OR 1.73 per 1.0 mg/L increase; 95% CI: 1.20–2.50; p = .003) were associated with a high 30-day mortality rate.ConclusionsPMT and CDT were associated with high revascularization rates and few complications. High plasma lactate and D-dimer may be associated with high 30-day mortality.